2012
DOI: 10.30638/eemj.2012.271
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agriculture on the Quality of Groundwater Resources in Peri-Urban Zone of Songon (Cote D'ivoire)

Abstract: The expansion of agro-industrial exploitations and the increased use of pesticides is a major concern for the quality of groundwater resources in the Abidjan area. The objective of this study is to assess the global vulnerability to pollution of these resources. Therefore, two methods based on the DRASTIC model were used. These methods are DRASTICLU and DRASTICLU-P in which land use is considered as a parameter, extending to 8 the number of analyze parameters in order to make the results more robust. To assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…This could be due to the high theoretical weight assigned to this factor (weight = 5). These findings are similar to those obtained by Dibi et al (2012), who have shown that, in addition to this parameter, topography, net recharge, and water table depth have a high impact on the vulnerability index. In addition, according to Samake et al (2011), the vadose zone and hydraulic conductivity had a significant impact on the vulnerability index that appears to have a moderate sensitivity to the deletion of water table depth (1.48 %), net recharge (1.36 %), and hydraulic conductivity (1.25 %).…”
Section: Sensitivity Of the Drastic Indexsupporting
confidence: 91%
See 1 more Smart Citation
“…This could be due to the high theoretical weight assigned to this factor (weight = 5). These findings are similar to those obtained by Dibi et al (2012), who have shown that, in addition to this parameter, topography, net recharge, and water table depth have a high impact on the vulnerability index. In addition, according to Samake et al (2011), the vadose zone and hydraulic conductivity had a significant impact on the vulnerability index that appears to have a moderate sensitivity to the deletion of water table depth (1.48 %), net recharge (1.36 %), and hydraulic conductivity (1.25 %).…”
Section: Sensitivity Of the Drastic Indexsupporting
confidence: 91%
“…Most of these techniques are based on analytic tools to associate groundwater contamination with land operations. There are three types of evaluation methods: process-based simulations, statistic procedures, and overlay and index approaches (Neshat et al, 2014;Dixon, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the high theoretical weight allocated to this factor (weight = 5). These findings are similar to those obtained by Dibi et al (2012) who have shown that in addition to this parameter, topography, net recharge, and water table depth have a high impact on the vulnerability index. Also, in Samake et al (2011) study, the impact of the vadose zone and the hydraulic conductivity parameters had a considerable impact on the vulnerability index.…”
Section: Sensitivity Of the Drastic Modelsupporting
confidence: 91%
“…Several methods have been adopted to assess the vulnerability. There are DRASTIC [5], GOD [6], AVI [7], SINTACS [8] and many other small methods including the properties of the environment (DISCO, DRASTIC-fm, DRATIC-P, DRASTICLU) have been studied [9]. However, all these methods, although effective, only allow the evaluation of vulnerability to pollution in a punctual way, i.e.…”
Section: Introductionmentioning
confidence: 99%